PARADIGMA ISLAM WASATHIYAH SEBAGAI STRATEGI MENJAGA KEHARMONISAN KEHIDUPAN BERBANGSA DAN BERNEGARA - Irwansyah; M. Sidik (LPPM-IAI BATAM, 2022)
Indonesia is a country with the most diverse levels in the world. Since the beginning, the Indonesian people have realized that this diversity will be a very frightening specter if it cannot be knitted properly. With this awareness, Indonesia's founding fathers then formulated a national philosophy with the term Bhineka Tunggal Ika, meaning that different is still one. and thus, it is undeniable that Indonesia's diversity is often the trigger for conflicts here and there. Especially if the conflict propaganda being played is labeled with religion. As it is known that in Indonesia, there are several religions that have been inaugurated by the government, and Islam is one of them. As the religion with the largest number in Indonesia and the world, the true existence of Islam in Indonesia is very positive. However, it is undeniable that in the midst of a moderate and compassionate ummah, there are actually a number of hardline numbers surrounding it. In fact, these hard-line groups often campaign for their understanding that is contrary to the regulations and provisions of this nation. For this reason, the birth of the wasathiyah Islamic paradigm is a relevant solution to dispel the movements that are played by a number of hard-line groups in Indonesia. And this study concludes that the wasathiyah Islamic paradigm is a very relevant paradigm in the midst of current globalization. and a peaceful, cool and prosperous national life can be bridged through the implementation of the wasathiyah Islamic paradigm.